2007
DOI: 10.1016/j.jacc.2006.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Both Coronary Calcium Scanning and Exercise Myocardial Perfusion Scintigraphy

Abstract: Among patients with nonischemic MPS studies, high CAC scores do not confer an increased risk for cardiac events. Thus, although patients with high CAC scores may be considered for intensive medical therapy to prevent future coronary artery disease events, a normal MPS study in such patients suggests no need for more aggressive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 41 publications
5
66
3
3
Order By: Relevance
“…Rogandi et al (34) found no increase in cardiac events at a mean of 32 mo in 1,089 nonischemic patients with high cardiac calcium scores (.1,000). However, in a study of more than 1,000 patients followed for nearly 7 y (35), cardiac events increased with high cardiac calcium score (.400) in patients with both normal and abnormal SPECT results, with separation of survival curves at 3 y for cardiac events and 5 y for death or MI.…”
Section: Contemporaneous Coronary Calcium Screeningmentioning
confidence: 97%
“…Rogandi et al (34) found no increase in cardiac events at a mean of 32 mo in 1,089 nonischemic patients with high cardiac calcium scores (.1,000). However, in a study of more than 1,000 patients followed for nearly 7 y (35), cardiac events increased with high cardiac calcium score (.400) in patients with both normal and abnormal SPECT results, with separation of survival curves at 3 y for cardiac events and 5 y for death or MI.…”
Section: Contemporaneous Coronary Calcium Screeningmentioning
confidence: 97%
“…More importantly, a normal perfusion scan is associated with a good prognostic outcome, even in the presence of extensive coronary atherosclerosis. 18 The findings of the study by Adamu et al suggest that the converse is also true, i.e., not only is it possible to see severe perfusion defects in patients without anatomically significant coronary lesions, but such defects are also of prognostic importance.…”
Section: Discordance Between the Anatomical And Functional Aspects Ofmentioning
confidence: 99%
“…The other study of false-negative MPI results in patients with a very high CAC score of >1,000 was by Ghadri et al [29] whose patients underwent ICA. Singlevessel disease was more prevalent in the study by Ghadri [31] assessed the frequency of cardiac death and myocardial infarction over a mean follow-up of 32±16 months in 1,153 patients undergoing both CAC scanning and MPI. Of these patients, 140 (28 ischemic, 112 nonischemic) had a CAC score>1,000.…”
Section: Index Casementioning
confidence: 99%